Traduções ficcionais: poéticas da oralidade do culto xangô do Recife - Carneiro, Tom Jones da Silva (2018)
If the area of Translation Studies in Brazil, by its very interdisciplinary nature, has broadened the dialogue with other areas, there is still much to be researched, especially regarding the cultural nature of the discipline (SALGUEIRO, 2015) and its role in the maintenance of cultures and traditions (RISÉRIO, 1993; 1996). An approach from the field of Anthropology is fundamental in this sense, especially in dialogues that investigate the influence and function of translation in the maintenance of cultural traditions, with emphasis on studies related to orality and the production of oral literature, orature (BROSE , 2015). This study intends to investigate the songs currently sung in the Xangô do Recife cult, comparing them to those collected and translated by Carvalho (1993). The point of view will be their relationship with myth (MALINOWSKI, 1986 and ALLEAU, 1976) and performance (FINNEGAN, 1982). In this analytical process, I shall compare the ''fictional'' translations with ''literal'' translations. ''Fictional'' translations are reinterpretations of the semantic content of the original texts in the current performance and reception environment and which were carried out by worshipers. I intend to identify how the meaning has changed or has been recreated. It is my intentionto analyse the strategies used by worshipers in creating their "fictional" translations, pointing out clues to understand how Candomblé sees and interprets the world. I shall investigate how and in what environment the "fictional" translations '' arise, and when they differ from the ''literal'' ones, to what extent they do so and under the influence of which aspects. The "fictional" translations are seen from the perspective of “poetic transcreation” as proposed by Campos (1962; 1967; 1984; 1985; 1987). This research intends to open new vistas for the Afro- Brazilian oral traditions from the point of view of a theory of oral poetry (ZUMTHOR, 2010). I believe that this new theoretical interface might broaden the understanding of key concepts of Translation Studies, such as the translator and the work (CHARTIER, 2012), in addition to contributing to a better understanding of the concept of "fictional" translation introduced by Carvalho in his study.